Tutors’ chronological age and characteristics as predictors of creative nurturing behavior in the 21st-century classroom - Mahama, Inuusah; Dampson, Dandy George; Eshun, Peter (Frontiers in Education, 2023)
Introduction The study examined tutors’ characteristics and chronological age as they influenced their creativity nurturing behaviors. Methods The descriptive cross-sectional design was used to survey 340 tutors (male = 220, female = 120) from 16 colleges of education. The data for the study were gathered using adapted versions of teachers’ characteristics and creativity nurturing behaviors scales. The data were analyzed inferentially. Results The study revealed that tutors’ characteristics influenced their creativity nurturing behaviors and teachers with 30 years and above of teaching could influence their creativity nurturing behaviors. Differences were established in tutors’ creativity nurturing behaviors based on their experience but such were not found in tutors’ characteristics. Discussion It was concluded that tutors’ characteristics and age are two key drivers of their creative abilities in the 21st century classroom. Therefore, management of teacher training institutions must cultivate an appreciable and appropriate tutor characteristics and dispositions so that they can use them to nurture trainee-teachers.